The Influence of Budget Planning, Bureaucratic Environment and Budget Evaluation on Budget Absorption with Management Commitment as a Moderator at the Directorate of Yogyakarta State University - Iin Herlina (International Journal of Economics, Commerce, and Management, 2025)
This research is research with a quantitative approach carried out at the Directorate of Yogyakarta State University. This research aims to determine whether or not there is an influence of budget planning, bureaucratic environment, budget evaluation on budget absorption with management commitment as a moderator. The data collection method in this research is a questionnaire. The sampling method used was the purposive sampling method. The population that was the object of research was the financial planning and management team at the Directorate of Yogyakarta State University. The sample in this study was 100 members of the Directorate of Yogyakarta State University. Hypothesis testing was carried out with Partial Least Square (PLS) through the SmartPLS 4.0 program. Based on the research results with a significance level of 5%, the conclusions obtained are: (1) There is a positive and significant influence of Budget Planning on Budget Absorption with at statistic of 3.255 and a significant value of 0.001; (2) There is a positive and significant influence of the Bureaucratic Environment on Budget Absorption with at statistic of 2.410 and a significant value of 0.008; (3) There is a positive and significant influence of Budget Evaluation on Budget Absorption with at statistic of 1.688 and a significant value of 0.046; (4) Management Commitment strengthens the positive influence of Budget Planning on Budget Absorption with at statistic of 2.071 and a significant value of 0.019; (5) Management Commitment does not strengthen the positive influence of the Bureaucratic Environment on Budget Absorption with at statistic of 0.534 and a significant value of 0.297; (6) Management Commitment strengthens the positive influence of Budget Evaluation on Budget Absorption with at statistic of 1.685 and a significant value of 0.046.